Quality of ‘Royal Gala’ cut apple during osmotic dehydration - Pieters,Bert (2020)
Abstract The present work aimed to evaluate quality parameters of ‘Royal Gala’ apple cubes during osmotic dehydration (OD). We investigated the following OD conditions: osmotic agent, pressure, and temperature. The osmotic agent, being lower after OD with sorbitol than sucrose solutions, mainly influenced the water activity of the product. The color changes increased with increased temperature and were higher in vacuum experiments than at atmospheric pressure. In general, we recommend OD at 25 °C and atmospheric pressure for the preservation of the total phenolic content (TPC) and antioxidant activity (AA) of apple cubes during the process. Peleg’s model was found to provide the best fit of TPC and AA data.